Effects of Trauma Bonding, Emotional Dependence, and Self-Esteem on Marital Persistence - Derah Sudjaniah; Bintoro Ariyanto; Indira Sascha; Melva Arita; Arum Yulistiyaningsih (Kajian Psikologi dan Kesehatan Mental, 2026)
Purpose: This study analyzes the influence of trauma bonding, emotional dependence, and self-esteem on relationship persistence in unhealthy marital relationships. Research Methodology: This research employed a quantitative explanatory design with a longitudinal time-lagged approach. Data were collected via online questionnaires distributed through Google Forms to individuals who had experienced unhealthy marital relationships. A purposive sampling technique was applied, resulting in 200 respondents. Data were analyzed using Partial Least Squares Structural Equation Modeling (SEM-PLS) with SmartPLS 4. Results: The findings show that trauma bonding and emotional dependence positively affect relationship persistence in unhealthy relationships. Conversely, self-esteem negatively affects relationship persistence. Individuals with stronger emotional attachment and dependence are more likely to remain in unhealthy relationships, while higher self-esteem reduces this tendency. Conclusions: Psychological factors significantly explain why individuals persist in unhealthy relationships. Trauma bonding and emotional dependence increase persistence, whereas self-esteem reduces it. Limitations: The study is based on self-reported data and focuses only on unhealthy marital relationships, limiting generalizability. Contributions: This study contributes to relationship psychology and mental health literature by proposing an integrative model of relationship persistence. The findings provide insights for psychologists, counselors, and practitioners in understanding abusive relationship dynamics.